The relationship between autistic traits, expressiveness, readability and social perceptions. - Rabi Samil Alkhaldi; Elizabeth Sheppard; Zack Ellerby; Emily Rachel Reed Burdett; Peter Mitchell (PLoS ONE, 2024)
This study investigated the relationship between autistic traits, expressiveness, readability (both actual and perceived), social favourability, and likability. Sixty participants designated as 'targets' were video recorded in a range of social scenarios and their autistic traits were measured using the Autism Spectrum Quotient. The videos were then shown to 106 new participants designated 'perceivers', who were split into three groups to make judgments related to readability, expressiveness, and social favourability respectively. Mediation analyses revealed that autistic traits negatively impacted both perceived likeability and social favourability, mediated by lowered expressiveness. Autistic traits also directly impacted readability, which was not mediated by expressiveness. The findings show how the level of autistic traits of a target can influence how they are socially perceived by others.